Pengembangan Media Interaktif berbasis Penemuan Terbimbing ‘TransGeo’ pada Materi Translasi untuk Siswa Kelas XI - Sebti Mardiana; Abd Qohar (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2017)
The research is developmental research aimed to produce interactive media based on guided discovery learning on translation for XI grade students. Media is in form of web-pages which embed flash file and Geogebra applet in presenting material. The research uses model of multimedia development by Alessi and Trollip. Validation test’s result shows that media is valid with score of 76,25%. In other hand, product trial to students and pupil shows that media is practicable with score of 84,46%. Hence, media developed satisfies quality aspect namely valid and practicable. Research also shows that media can facilitate as well as motivate students’ learning. The use of media especially by ulitizing mathematical software with discovery learning method is highly suggested to be applied in mathematics instruction.